A sensitive electrochemical sensor for glutathione based on specific recognition induced collapse of silver-contained metal organic frameworks - Li, Wenjie; Xu, Zhenjuan; Li, Peipei; Liu, Xiang; Chen, Chao; Zhang, Youyu; Liu, Meiling; Yao, Shouzhuo (Mikrochimica acta (1966), 2024)
An electrochemical sensor capable of detecting glutathione (GSH) with high sensitivity and selectivity was developed based on the unique novel electroactive silver-based metal organic framework (Ag-MOF). The Ag-MOF obtained by silver nitrate and 1,3,5-benzoic acid (H 3 BTC) was thoroughly characterized and was modified onto the electrode via facile drop-casting method. The electrochemical response of GSH on the Ag-MOF modified electrode showed a significant reduction in the current signal because the Ag-GSH complex had stronger specific affinity than Ag-H 3 BTC and resulted in the collapse of the Ag-MOF. This sensor demonstrated an extensive linear dynamic range of 0.1 nM-1 µM, along with the low detection limit of 0.018 nM. Additionally, it exhibited good reproducibility, stability, and resistance to interfering compounds. The Ag-MOF modified electrode demonstrated superior performance attributed to its rapid electron transfer rate, outstanding electrochemical redox activity, and specific recognition/competitive reaction. These factors improved both sensitivity and selectivity. The high anti-interference ability allowed for the selective detection of GSH in intricate surroundings. In the real sample testing, the RSD was lower than 3.1% and the recovery was between 98.1 and 103%. This research highlights the potential of Ag-MOFs in developing electrochemical sensors and their promising applications in determining GSH for food screening and early disease diagnosis.